Political Parties and Electoral Volatility: How (un)stable is the Albanian Electorate? - Reli, Alban; Xhaferaj, Anjeza (Advances in Social Sciences Research Journal, 2024)
This paper offers an in-depth analysis of electoral volatility in Albania from 1991 to 2021, a transformative period from a communist regime to a democratic multi-party system. It diverges from Central and Eastern European trends by examining Albania’s unique political dynamics and the factors influencing electoral behavior and volatility. Utilizing the Pedersen Index, the study methodically evaluates various determinants impacting party electoral volatility in Albania. The research underscores the significance of high membership rates and robust ground organization within major political parties as key contributors to low volatility levels in Albania’s party system, thus providing insight into the intricacies and idiosyncrasies of Albania’s political landscape.